Perceived depth modulates allocation of attention - Tasfia Ahsan; Laurie M. Wilcox; Erez Freud (Scientific Reports)
Abstract There is growing evidence that the visual system processes objects perceived as closer more quickly and accurately than those farther away, a phenomenon known as the “close advantage effect” (CAE). The mechanisms underlying this effect, however, remain unknown. In this series of studies, we assessed whether perceived depth modulates allocation of attention. Using a Posner cueing task in Experiment 1a, we found greater accuracy for close surface targets (demonstrating the CAE). Critically, we also found a smaller Posner effect in the close surface, suggesting that attentional resources are better utilized in this space. Experiment 1b confirmed that these results were not due to differences in background surface sizes. In Experiment 2a, using the Egly-Driver task, we replicated and extended the results of Experiment 1a. Participants were more accurate when shifting attention from far to close surfaces and when shifting attention within the close surface, compared to when shifting attention within the far surface. These results suggest that perceived proximity makes attentional shifts more efficient. This effect persisted in Experiment 2b, even after controlling for the perceived size of the targets. Overall, our findings show that perceived depth modulates attention, with close space receiving preferential processing likely due to its relevance for immediate interaction.